Tapping into Metabolomics for Understanding Host and Rotavirus Group A Interactome - Phiona Moloi Mametja; Mmei Cheryl Motshudi; Clarissa Marcelle Naidoo; Kebareng Rakau; Luyanda Mapaseka Seheri; Nqobile Monate Mkolo (Life)
Group A rotavirus continues to be a leading global etiological agent of severe gastroenteritis in young children under 5 years of age. The replication of this virus in the host is associated with the occurrence of Lewis antigens and the secretor condition. Moreover, histo-blood group antigens (HBGAs) act as attachment factors to the outer viral protein of VP4 for rotavirus. Therefore, in this study, we employed a metabolomic approach to reveal potential signature metabolic molecules and metabolic pathways specific to rotavirus P[8] strain infection (VP4 genotype), which is associated with the expression of HBGA combined secretor and Lewis (Le) phenotypes, specifically secretor/Le(a+b+). Further integration of the achieved metabolomics results with lipidomic and proteomics metadata analyses was performed. Saliva samples were collected from children diagnosed as negative or positive for rotavirus P[8] strain infection (VP4 genotype), which is associated with the HBGA combined secretor/Le(a+b+). A total of 22 signature metabolic molecules that were downregulated include butyrate, putrescine, lactic acid, and 7 analytes. The upregulated metabolic molecule was 2,3-Butanediol. Significant pathway alterations were also specifically observed in various metabolism processes, including galactose and butanoate metabolisms. Butyrate played a significant role in viral infection and was revealed to exhibit different reactions with glycerolipids, glycerophospholipids, sphingolipids, sterol lipids, and fatty acyls. Moreover, butyrate might interact with protein receptors of free fatty acid receptor 2 (FFAR2) and free fatty acid receptor 3 (FFAR3). The revealed metabolic pathways and molecule might provide fundamental insight into the status of rotavirus P[8] strain infection for monitoring its effects on humans.